2013
DOI: 10.1016/j.jvs.2012.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of restenosis following tibial artery endovascular interventions for critical limb ischemia

Abstract: TAEIs can be used successfully to treat patients with critical limb ischemia with acceptable limb salvage rates. Special attention should be given to patients with extensive tissue loss or gangrene because they are at risk for early restenosis and subsequent limb loss. Strict wound and hemodynamic surveillance, wound care, and timely reinterventions are crucial to achieve successful outcomes in this patient population. Amputation or alternative revascularization options, when feasible, should be considered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
2
28
0
4
Order By: Relevance
“…Other studies have reported restenosis and tissue loss, specifically gangrene, as predictors of negative outcome (14,27). Concomitant popliteal interventions were also identified as predictive of major amputation in the present series, probably reflecting disease extent rather than the effect of the intervention itself.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Other studies have reported restenosis and tissue loss, specifically gangrene, as predictors of negative outcome (14,27). Concomitant popliteal interventions were also identified as predictive of major amputation in the present series, probably reflecting disease extent rather than the effect of the intervention itself.…”
Section: Discussionsupporting
confidence: 48%
“…PTA results for CLI in the literature have already proven infrapopliteal PTA to be comparable to, if not better than, bypass surgery (7,(9)(10)(27)(28)(29)(30). PTA and bypass primary patency rates (33%-37% vs 63%), secondary patency rates (56%-63% vs 70%), and limb salvage rates (75%-100% vs 4 75%) have been reported in an update (25) and a meta-analysis (29), respectively, and, given the relative homogeneity of these data in the literature, an intercenter comparison of these techniques was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…De même, l'étude de Saqib et al également publiée en 2013, retrouvait que le taux de resténose après angioplastie tibiale était plus élevé en cas de gangrène (p = 0,03). En présence d'une ischémie critique stade 5 ou 6 de la classification de Rutherford, les auteurs recommandent donc une revascularisation par pontage chirurgical si les patients ne peuvent pas bénéficier d'une surveillance clinique hebdomadaire [37].…”
Section: L'angioplastie Transluminaleunclassified
“…En la población mundial existe una prevalencia entre el 3 al 18 % [3][4][5]15 . El manejo puede ser médico, quirúrgico o endovascular 16 .…”
Section: Discussionunclassified
“…En la población analizada de manera retrospectiva, se identificó que la edad de los pacientes en el momento de intervención, así como la presencia de comorbilidades identificadas en la literatura mundial es muy similar, con una media cercana a la séptima década de la vida y predominantemente en el sexo masculino 14,15 . Así mismo, se observó mayor distribución del compromiso inicial en territorio vascular con nuevos episodios de estenosis presentados en mayor cantidad en pacientes con compromiso mixto (supra e infragenicular), seguido por los de compromiso infragenicular, con similares resultados respecto a las publicaciones de la literatura 1 , en las que, según Ruby, se presenta desde un 37 a 50 % de estenosis en el infrapoplíteo.…”
Section: Discussionunclassified